Previous Preterm Birth and Current Maternal Complications as a Risk Factor of Subsequent Stillbirth. (30th July 2015) - Ibrahimou, Boubakari; Anozie, Cynthia; de la Cruz, Cara; Salihu, Hamisu
Abstract : Purpose. To examine the association between previous preterm birth and the risk of stillbirth. Methods. This population-based retrospective cohort study analyzed live births and stillbirth records in Missouri (1989–1997). The main outcome of interest was stillbirth occurrence while the exposures were prior preterm birth. Adjusted odds ratios and 95% confidence intervals were computed using logistic regression. Results. Women who had a previous preterm birth have 63% increased odds of stillbirth in singleton pregnancies and 75% increased odds in twins as compared to those who did not have a preterm birth in a prior pregnancy (AOR = 1.63, 95% CI = 1.41–1.88 and AOR = 1.75, 95% CI = 1.20–2.56), respectively. The most significant risk factor for stillbirth in singleton pregnancies was uterine bleeding (AOR = 5.89, 95% CI = 5.13–6.76). In twin pregnancies, it was the condition hydramnios/oligohydramnios (AOR = 4.72, 95% CI = 3.70–6.02). Eclampsia was associated with a heightened risk of stillbirth in singletons (AOR = 2.45, 95% CI = 1.41–4.12), but not in twins (AOR = 0.96, 95% CI = 0.13–7.00). Black mothers were more likely than white to experience stillbirth (AOR = 2.10, 95% CI = 1.99–2.22 for singletons and AOR = 1.51, 95% CI = 1.27–1.79 for twins). Conclusion. Stillbirth is a vital public health issue and its etiology is not well understood. Previous history of preterm birth was found to be associated with future stillbirth. Targeted early medical and obstetric care and interventions among women with preterm birth history may potentially reduce the likelihood of stillbirth.